E-Learning in the Geography, Earth, and Environmental Sciences Disciplines: Practitioner Perspectives from the United Kingdom - France, Derek; Fletcher, Stephen (Journal of Geography Education, 2007)
This paper provides an overview of the findings from a national survey of geoscience practitioners based in universities in the UK to establish the current use, re-use and development of e-learning materials. The research was funded and co-ordinated by the Higher Education Academy Subject Centre for Geography, Earth and Environmental Sciences. Motivations to develop e-learning materials in the geoscience community primarily related to improvements in personal and teaching efficiency, but there were numerous barriers impeding the realisation of such benefits. Barriers included limited technical and pedagogic knowledge, a lack of departmental and institutional support, and concern over the time required to develop new materials. The specificity of e-learning resources was also found to mitigate against sharing and re-using materials. If e-learning is to play a serious role in educating future generations of geoscientists, support must continue and be enhanced.